(untitled) (Global Journal of Medical Research, 2023)
Introduction When analyzing the main depressive conditions and their treatments we understand that it is not so simple to take care of psychosomatic conditions because it is a pathology that has a significant epidemiological aspect and needs a good approach therefore psychedelic drugs come in as a an important alternative as a treatment Methodology This is a literature review with research in databases using 60 scientific articles as a basis and being filtered based on scientific impact and approach Results Psychedelic agents are chemical substances that in non-toxic doses produce changes in conception and thinking in a state of mind thus altering perception and reason